2023
DOI: 10.3390/catal13030493
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Furan-Based Visible Light Photoinitiators of Polymerization

Abstract: Photopolymerization is an active research field enabling to polymerize in greener conditions than that performed with traditional thermal polymerization. At present, a great deal of effort is devoted to developing visible light photoinitiating systems. Indeed, the traditional UV photoinitiating systems are currently the focus of numerous safety concerns so alternatives to UV light are being actively researched. However, visible light photons are less energetic than UV photons so the reactivity of the photoinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 263 publications
0
4
0
Order By: Relevance
“…It is worth remarking the very low amount of photoinitiator needed as compared to the conventional photoinitiator systems which are added in a typical dose of 1−5 wt %. 27 Control experiments demonstrated that both light and CPNs are necessary to achieve polymerization (Figure S3).…”
Section: Synthesis and Characterization Of Conjugated Polymer Nanopar...mentioning
confidence: 99%
“…It is worth remarking the very low amount of photoinitiator needed as compared to the conventional photoinitiator systems which are added in a typical dose of 1−5 wt %. 27 Control experiments demonstrated that both light and CPNs are necessary to achieve polymerization (Figure S3).…”
Section: Synthesis and Characterization Of Conjugated Polymer Nanopar...mentioning
confidence: 99%
“…The lone pairs of electrons on the oxygen and sulfur atoms can engage in p−π conjugation with the double bond in the ring, leading to the formation of a delocalized π bond. This characteristic makes these heterocyclic compounds effective chromophores, enhancing the light absorption capability of molecules. Karace et al synthesized a series of type II PIs of thiophene conjugated with thioxanthenone. The absorption of these molecules was red-shifted to 460 nm compared with thioxanthenone, and when complexed with tertiary amines, such molecules could efficiently initiate the polymerization of MMA.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers 2023, 15, x FOR PEER REVIEW 2 of 4 [24,[59][60][61][62][63][64], dithienophosphole derivatives [65], thioxanthones [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80], benzophenones [81][82][83][84], cyanines [85], bodipy [66,[86][87][88][89][90], NIR dyes [91], anthraquinones [92], curcumin [93][94][95][96], furan derivatives [97], pyrenes [98][99][100][101], iodonium salts [66,[102][103][104][...…”
Section: Introductionmentioning
confidence: 99%